Integrative approach for enhanced ovarian cancer diagnosis: cytology and biomarkers - Shuangyan Chen; Lixiu Cai; Daoyin Zhou; Yan Chen (Discover Oncology)
Abstract Background This study evaluates the diagnostic value of routine cytology and liquid-based cytology (LBC) in detecting malignant cells in ovarian cancer-associated serous effusions and explores the clinical significance of CA125 and CA153 in single and combined serum biomarker testing. Methods Serous effusion samples (ascites: n= 104, pleural effusions: n= 11) from 115 confirmed ovarian cancer patients underwent routine cytology and LBC,with positivity rates compared. Serum CA125 and CA153 were analyzed in 108 patients, assessing their correlation with cytology results. Cytology positivity was defined as the presence of malignant cells, regardless of clustering. Clusters of ≥3 malignant cells were also recorded for morphological analysis. Serum CA125 > 35 U/mL and CA153 > 25 U/mL were considered positive. McNemar’s test evaluated the diagnostic performance of biomarkers alone and in combination, while Spearman’s correlation assessed the relationship between malignant cell count and serum CA125/CA153 levels. Results The positivity rates for routine cytology and LBC were 72.17% (83/115) and 66.96% (62/92), respectively (P > 0.05). CA125 positivity (93.51%, 101/108) was significantly higher than CA153 (64.35%, 66/101), P < 0.01. CA125 + CA153 combined testing improved sensitivity to 96.30% (P < 0.05). Malignant cell count correlated poorly with serum CA125 (r = 0.210, P > 0.05). Bacterial (n = 2) and fungal (n = 1) pathogens were identified in cytological analysis alongside significant morphological heterogeneity of malignant cells. Conclusion Routine cytology effectively detects malignant cells in ovarian cancer serous effusions, while CA125 shows high sensitivity but limited standalone diagnostic value. LBC offers no additional advantage. CA125/CA153 combined testing significantly enhances diagnostic accuracy, particularly in advanced cases. Graphical Abstract